Text Message Interventions for Physical Activity: A Systematic Review and Meta-Analysis - Smith, Diana M.; Duque, Laura; Huffman, Jeff C.; Healy, Brian C.; Celano, Christopher M. (American journal of preventive medicine, 2020)
Despite clear health benefits, many individuals fail to achieve the recommended levels of physical activity. Text message interventions to promote physical activity hold promise owing to the ubiquity of cell phones and the low expense of text message delivery. A systematic review and meta-analysis were performed to examine the impact of text message interventions on physical activity. Searches of PubMed, PsycINFO, Scopus, Cochrane, and ClinicalTrials.gov databases from inception to December 2017 were performed to identify studies investigating one-way text message interventionss to promote physical activity. A subset of RCTs, including an objective (accelerometer-based) physical activity outcome, were included in random-effects meta-analyses in 2018. The systematic search revealed 944 articles. Of these, 59 were included in the systematic review (12 1-arm trials and 47 controlled trials; n=8,742; mean age, 42.2 years; 56.2% female). In meta-analyses of 13 studies (n=1,346), text message interventionss led to significantly greater objectively measured postintervention steps/day (Cohen's d=0.38, 95% CI=0.19, 0.58, n=10 studies). Analysis of postintervention moderate-to-vigorous physical activity found a similar but not statistically significant effect (Cohen's d=0.31, 95% CI= −0.01, 0.63, n=5 studies). Interventions with more components, tailored content, and interventions in medical populations led to nonsignificantly larger effect sizes compared with text message interventions without these features. Text message interventions lead to higher objectively measured postintervention physical activity compared with control groups. More extensive, well-controlled studies are needed to examine this relationship further and identify characteristics of effective text message interventions.